Unlocking the potential of site based mobility management through Local Travel Plan Groups - Marcus Enoch; Lian Zhang; Stephen Ison (2007)
Travel Plans are potentially an important means by which excessive car use can be addressed. They involve traffic generators such as retail parks, hospitals and local authorities and are seen as a relatively cheap and uncontroversial measure that can be introduced in a targeted and site-specific manner. They are however predicated on these organisations being motivated embrace travel plans in helping to address a problem, for example congestion, which they may not see themselves as being the major cause of. One way of addressing the resistance of organisations to meaningfully adopt travel plans is for local authorities to set up some form of ‘Local Travel Plan Group’ (LTPG) or ‘Network’ offering organisations more influence as to how local transport decisions are enacted. The aim of this paper is to detail the reasons why the widespread adoption of travel plans has failed to materialise and whether establishing LTPG’s is likely to aid the situation. The paper classifies LTPG’s, explores how they might be implemented and what type is appropriate in what circumstances. The paper is based on a review of existing LTPG’s and their potential for effective policy transfer. The paper draws on research undertaken for the European Commission North West Europe Interreg IIIB programme OPTIMUM2.